Facile hydrothermal synthesis and optical properties of monoclinic CePO 4 nanowires with high aspect ratio - Ekthammathat N. (2014)
One-dimensional cerium phosphate (CePO 4) nanowires (NWs) were successfully synthesized by a facile and simple hydrothermal method at 200°C for 12 h, using Ce(NO 3) 3·6H 2O and Na 3PO 4·12H 2O as starting materials, and followed by pH adjusting to be 13 using HNO 3 (conc.). Phase, morphologies, and vibration modes of the as-synthesized CePO 4 products, characterized by XRD, SEM, TEM, and FTIR, were proved to be perfect and uniform monoclinic CePO 4 nanowires with aspect ratio of more than 250 for the product synthesized in the solution with the pH of 1. The UV-visible and photoluminescence (PL) spectrometers were used to investigate optical properties of the as-synthesized monoclinic CePO 4 nanowires. © 2012 Nuengruethai Ekthammathat et al.